Mucin Overproduction in Chronic Inflammatory Lung Disease - Hans-Peter Hauber; Susan C Foley; Qutayba Hamid (Canadian Respiratory Journal)
Mucus overproduction and hypersecretion are commonly observed in chronic inflammatory lung disease. Mucins are gel-forming glycoproteins that can be stimulated by a variety of mediators. The present review addresses the mechanisms involved in the upregulation of secreted mucins. Mucin induction by neutrophil elastase, bacteria, cytokines, growth factors, smoke and cystic fibrosis transmembrane conductance regulator malfunction are also discussed.